Narratives on access to higher education : educational leadership looking beyond barriers - Ramamoorthi, Bhavani (2017)
This research aims to understand the social, economic and political complexities that surround a learner’s access to higher education in South Africa. The objective of the study is therefore to particularly examine the enabling and constraining factors in accessing higher education for the participants in the study. The study looks at the experiences of four young men and women (two men and two women) from South Africa that led to their educational achievements. It weaves their success stories through the complex interwoven social, familial, school and community environments. The narratives have been observed in con-text to existing key educational leadership theories and mainly by evaluating the strengths of the transformational leadership, pedagogical leadership and leader-ship for social justice in creating a more equitable educational system. The research indicates that social inequalities in accessing higher education continue to persist. The data from the narratives reveals that it was the aspiration and motivation to achieve access to higher education that ultimately led the learners through these challenging environments. In thinking of these findings, educational leadership has the potential to respond by looking beyond the barriers to understand more of what enables these participants to access higher education. Progressive policies, intervention through capacity building, and involving stakeholder communities are useful, yet do not completely help address the complexities being faced in accessing higher education. The learners are agents of social change and it is important for educational leadership to perceive these learners in new light to address issues in access to higher education.